If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(x + -2) + 6x + -10 = 17 Reorder the terms: -3(-2 + x) + 6x + -10 = 17 (-2 * -3 + x * -3) + 6x + -10 = 17 (6 + -3x) + 6x + -10 = 17 Reorder the terms: 6 + -10 + -3x + 6x = 17 Combine like terms: 6 + -10 = -4 -4 + -3x + 6x = 17 Combine like terms: -3x + 6x = 3x -4 + 3x = 17 Solving -4 + 3x = 17 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 3x = 17 + 4 Combine like terms: -4 + 4 = 0 0 + 3x = 17 + 4 3x = 17 + 4 Combine like terms: 17 + 4 = 21 3x = 21 Divide each side by '3'. x = 7 Simplifying x = 7
| 0x+9=4 | | 60+15x=90 | | 6x+8x+10x-24=18 | | (x+2)+2(x-2)=4 | | -89-7=5x+187 | | (3x+5)-7=73 | | 8n+3=2n+15 | | 7-0.04[6p-(2-0.01p)]=43.404 | | 3x+.75x=318.75 | | 5+4r=-36 | | 5(x-2)=3(1+2x) | | 14+5x+3(-x+3)=11 | | 53+x=90 | | 5x-7=-3+x | | 5x-4y-3=0 | | AX-D+C-BX=0 | | 147=7m | | 7x+6(7x-10)= | | 9h-4=86 | | 10n+6n+9n=150 | | 3-3r=9 | | -10+2x=30 | | -(6a+a+3)=25 | | -5k+24=-1 | | 51+10x=90 | | (-6)2+2(-6)= | | 3*6-(4-7-2-7*6)= | | (11y-36)+63=180 | | 81+10x=90 | | 10x-6=21 | | 28-5x=x-4 | | 20+30x=36+b |